Pelatihan Pembuatan Minyak Daun Bawang Untuk Ibu-Ibu Rumah Tangga desa Sumbung Kecamatan Cepogo Kabupaten Boyolali - Nur Fadila; Ari Wahyono; Amy Wulandari; Sumiyati Sumiyati; Lutvia Tribuwana; Tri Widianto; Suhendra Suhendra; Putri Nawang Asri; Diva Amelia Merryana Putri; David Kadar Saputro; Aditya Santoso; Joko Warsito (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Boyolali is one of the districts in Central Java which is geographically located on two mountainous plains which are rich in natural potential. Cepogo subdistrict is part of Boyolali district which makes agriculture one of the main economic activities. As an effort to explore the economic potential hidden in leeks in Sumbung village, located in Cepogo sub-district, Boyolali Regency, training was held on making leek oil. Leek oil can be a high-value product with broad market potential. Leeks are used in cooking and have benefits for lowering cholesterol levels. The aim of this training is to improve the skills and knowledge of the Sumbung Village community in the leek oil production process and to initiate the development of new MSMEs in Sumbung Village. It is hoped that this training can help the community to utilize leeks more effectively and develop micro-enterprises at the household level.